High fatigue life and cooling efficiency of NiTi shape memory alloy under cyclic compression. (15th January 2019) - Zhang, Kuo; Kang, Guozheng; Sun, Qingping
Abstract: We investigate the cyclic compressive fatigue behavior of pseudoelastic polycrystalline NiTi shape memory alloy (SMA) under maximum applied stresses of 800, 950 and 1200 MPa. A fatigue life of over 20 million cycles under 800 MPa is recorded with an average coefficient of performance ( COP ) of 17.6. Rock-like splitting and chipping through nucleation and slow stable growth of compression-parallel cracks driven by very small stress intensity factor are the major fatigue failure modes of the material. The high fatigue life and cooling efficiency of NiTi SMA under cyclic compressive phase transformation provide a solid mechanical base for its application in solid-state cooling technology.